Adaptive multi-level explicit congestion notification. (15th November 2007) - Durresi, A.; Sridharan, M.; Jain, R.
We propose Adaptive Multi-level ECN (AMECN), a new TCP congestion scheme, as an extension to Multi-level Explicit Congestion Notification (MECN). AMECN allows network operators to achieve high throughput and low delays. However, AMECN performance depends its parameter settings and the level of congestion, hence, no guarantees can be given about delay. To achieve a predictable average delay with AMECN, constant tuning of the parameters to adjust to current traffic conditions is needed. We show how to tune AMECN parameters. The analysis of our simulations shows that Adaptive MECN performs better than Adaptive RED.